Process/industrial instruments and controls handbook - McMillan, Gregory K.; Considine, Douglas M. (McGraw-Hill handbooks, 1999)
The latest methods for increasing process efficiency, production rate, and quality. Award-winning editor Greg McMillan has loaded Process/Industrial Instruments and Controls Handbook, Fifth Edition, with advice from top technical experts to help you tackle process instrument and control assignments confidently and solve problems efficiently. This major revision of the bestselling on-the-job toolkit includes time-saving tables,selection ratings, key points, rules of thumb and hundreds of topic-defining illustrations. Updated to mirror the most common industry practices, it brings you up to speed on smart instrumentation and the latest advances sparked by increased power and miniaturization of the microprocessor. Thorough coverage of the Windows NT platform and Fieldbus... distributed control systems and field-based systems...knowledge-based operator training...instrument maintenance cost reduction and an overview of the ISA/IEC Fieldbus Standard help you get the most out of these major shifts in technology.